Evaluating Barriers to Viral Suppression among People with HIV in Santiago, Dominican Republic. (May 2022) - McCarthy, Meghan; Tao, Jun; Lerebours, Alain; Rodriguez, Claudia; Flanigan, Timothy P; Sanchez, Martha C
The Dominican Republic (DR) has the second-highest prevalence of HIV infection in the Caribbean, but viral suppression and treatment adherence are not well understood. We conducted a cross-sectional study among people living with HIV/AIDS(PLWHA) to fill in the knowledge gap. Questionnaire was used to collect demographic data, antiretroviral therapy (ART) adherence, and barriers and facilitators to HIV care. Viral load and other clinical information were extracted through chart reviews. Descriptive analyzes and logistic regression were conducted to explore factors associated with non-viral suppression and imperfect ART adherence. Of 193 PLWHA 83.9% were virally suppressed. Those that were non-virally suppressed were more likely of being male (odds ratio [OR]: 2.55, 95% confidence interval [CI]: 1.17-5.58) and less likely of being unemployed (OR: 0.28, 95% CI: 0.08-0.96). However, being male (OR: 0.78, 95% CI:0.40-1.53) and unemployed (OR: 0.28, 95% CI:0. 08-1.21) were less likely to report imperfect adherence. Tailored interventions are needed to improve adherence and viral suppression in DR.